THE ROLE OF HALAQAH REVIEW ON IMPROVING BASIC NAHWU LEARNING IN ISLAMIC SCHOOL MEDAN - Muhammad Ferdyandi Syahputra Lubis; Zulfahmi Lubis; Wahyudi Jambak (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
This research examines halaqah recitation's role in improving students' basic nahwu learning at the Islamic Center in Medan City, Deli Serdang Regency. The urgent issues that will be studied are the implementation of halaqah recitation, the improvement of basic nahwu learning, and the supporting and inhibiting factors for students' nahwu learning. This research aims to find out the process of implementing halaqah recitation, Nahwu learning at the Islamic Center, and the supporting and inhibiting factors for students' Nahwu learning. This research is a qualitative descriptive study with an educational approach and a psychological approach. The students of halaqah teachings have the demand method, the lecture method, the sorogan method, the recitation method, the rote method, and the role model method. The learning method is in studying Qawa'id or nahwu, namely qiyasiyah and istiqraiyah tariqah. The research methods are observation, interviews, and documentation. The results of this study indicate that halaqah recitation at the Islamic Center is important in improving students' basic nahwu learning. Students already know the basic nahwu rules and can determine the position of words in certain books. The result is about the supporting factors of nahwu learning and the inhibiting factors of interest. تبحث هذه الدراسة في دور تلاوة الحلقة في تحسين تعلم الطلاب الأساسي للراهوية في مركز المدرسة الداخلية الإسلامية في مدينة ميدان ، ديلي سيردانج ريجنسي. المشاكل العاجلة التي ستتم دراستها هي تنفيذ تلاوة الحلقة ، وتحسين تعلم اللغة الأساسي ، بالإضافة إلى العوامل الداعمة والمثبطة لتعلم الطلاب. الغرض من هذا البحث هو معرفة عملية تنفيذ تلاوة الحلقة ، وتعلم اللغة في المركز الإسلامي ، بالإضافة إلى العوامل الداعمة والمثبطة لتعلم طلاب اللغة العربية. هذا البحث دراسة وصفية نوعية ذات منهج تربوي ومنهج نفسي. يصنف هذا النوع من البحث على أنه نوع من البحث الميداني. تقنيات جمع البيانات في البحث باستخدام الملاحظة والمقابلات والتوثيق. تشير نتائج هذه الدراسة إلى أن دراسة الحلقة في مركز المدرسة الداخلية الإسلامية تلعب دورًا مهمًا في تحسين تعلم اللغة الأساسية للطلاب ، ويمكن ملاحظة أن الطلاب يعرفون بالفعل القواعد الأساسية وقادرون على تحديد موضع الكلمات الواردة في كتب معينة. يتم اختبار العوامل الداعمة لتعلم النهو بعيدًا عن دراسة الحلقة ، مثل تخصص اللغة العربية ، ومسابقة قراءة كتب ، والقرى العربية وغيرها من البرامج اللامنهجية وكذلك الكتب التي تمت دراستها في تلاوة الحلقة في امتحانات الفصل الدراسي الفردية والزوجية. العامل المانع هو عدم اهتمام بعض الطلاب ، لذلك يكون لديهم دافع أقل للمشاركة في عملية تلاوة الحلقة